DECONSTRUCTION OF CARTESIAN DUALISM IN SENSORY PERCEPTION - Diaz Supandi, Muhammad; Elit Ave Hidayatullah (MIYAH: Jurnal Studi Islam, 2025)
Abstract:This study aims to deconstruct Cartesian dualism, which has dominated Western epistemology, particularly in understanding the relationship between the mind, body, and sensory perception, leading to a passive and mechanical view of perception. The research offers a solution from the perspective of holistic Islamic epistemology, grounded in the concept of tawhid (oneness). The main objectives are: (1) to critically analyze the tension between Cartesian dualism and Islamic epistemology using maq??id? exegesis of Qur'anic verses, (2) to formulate an alternative framework based on Islamic tur?th, known as "Enactive Tawhidic Perception," positioning the senses as active agents in constructing reality, and (3) to explore the neuroscientific implications of this model. The qualitative library research method focuses on primary texts such as I?y?’ ‘Ul?m al-D?n by Al-Ghazali, Al-Asf?r al-Arba’ah by Mulla Sadra, and maq??id? exegesis to understand the Qur'anic perspective on perception. The study shows that Islamic epistemology views perception as an integrated activity involving the senses, intellect, and heart as a unified epistemic system, where the senses are not passive but active agents in understanding reality. This research introduces a new paradigm for the neuroscience of spirituality, suggesting that perception can be a means to draw closer to God. In conclusion, this study presents the "Enactive Tawhidic Perception" model, bridging science and spirituality, and enriching contemporary Islamic cognitive philosophy by offering solutions to the fragmentation in understanding sensory perception. Keywords: Dualism Cartesian, Islamic epistemology, Neurosains, Spirituality